Seasonal effects of plant functional groups on molecular biogeochemistry of dissolved organic matter in porewater of a poor fen - Song, Zhimin; Khaksari, Maryam; Lilleskov, Erik A.; Kane, Evan S.; Doskey, Paul V. (Frontiers in Environmental Science, 2025)
Climate change may transform peatlands from net carbon (C) sinks to C sources, which could result in a positive feedback to global warming. Warmer temperatures might lower water tables, increase the abundance of shrubs, slow Sphagnum and sedge growth and further accelerate the decomposition of dissolved organic matter (DOM) with a concomitant release of C from the surface. Studies in which vascular plant functional groups (PFGs) in peatlands have been manipulated to mimic the potential effects of a warming climate on DOM are scarce. In the subject study, seasonal effects of PFGs on the molecular composition of DOM of peat porewater were investigated in manipulated plots of a poor fen in Nestoria, Michigan, United States. The organic molecular composition of the peat porewater exhibited strong interactions with PFG and season. Monomeric substances (e.g., monosaccharides and amino acids), which are found in root exudates and are also the products of decomposition of polymeric substances, were least abundant early in the growing season and increased in abundance late in the season. High levels of DOC and proteinaceous substances and an unlikely abundance of total phenolic substances in sedge plots with Sphagnum were attributed (1) to rapid decomposition of labile compounds in the oxygen-rich microenvironment surrounding sedge roots and preservation of more recalcitrant substances or (2) to contributions of lignin-like substances by Sphagnum. Tannin- and lignin-like compounds in the Ericaceae plots with Sphagnum were attributed to inputs of the woody biomass. The refractory organic substances apparently persisted due to a combination of rhizosphere anoxia and suppression of free-living saprotroph activity by the Ericoid mycorrhizal fungi. Through a novel analytic approach, which included organic compound class analysis, determination of spectral indices, and molecular analysis by ESI-UHR-MS, we observed indirect evidence of the complexation of proteinaceous substances by tannin-like substances and the apparent reaction of phenolic moieties of lignin-like substances with amino sugars. A synergistic effect between sedge and Ericaceae was likely responsible for rapid decomposition of DOM in plots with Sphagnum in which vascular PFGs were unmanipulated. Observing the effects of vascular PFGs on seasonal variations of the molecular composition of DOM will improve predictions of the short- and long-term storage of C in peatlands in a changing climate.